The effect of different training programs on throwing accuracy of elite female handball players - Eler, N.; Eler, S. (International Journal of Human Sciences, 2017)
The aim of this study is to examine the acute effect of different training programs applied to elite female handball players on throwing accuracy. 14 elite female players were participated in the study. The mean age of the participating players was 28.64 ± 9.88 (years), the mean height length was 176.50 ± 4.86 (cm), the mean body weight was 68.07 ± 2.12 (kg) and the mean sport age was 14.36 ± 4.89 (years). On different days, a technical training program, maximal strength training program, strength endurance training program and speed power training program have been implemented to the participating players in the research. Before and after training, the players throwing the ball from their area to the specific points of goal and the percentage of accuracy was determined. As a result; there was a significant difference between before and after maximal strength training the mean values of throwing accuracy (p<0,05) but there was no significant difference before and after other training programs (p> 0,05). This result indicates that acute maximal strength training has a negative effect on throwing accuracy.